The Consolidated Medium-Term Income and Expenditure Framework. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
The medium-term income projections have been updated from the April 2015 outlook and the February review of the adequacy of precautionary balances. The main changes to the outlook stem from a more gradual rise in the SDR interest rates and lower surcharge income following the lowering of the surcharges threshold. The revised projections still show a positive forecast for net operational income (and surcharges) over the medium term, albeit lower than projected a year ago. Lending income (excluding surcharges) is marginally higher compared with earlier estimates. Surcharge income is estimated to be lower, reflecting the adjustment of the surcharges thresholds following the implementation of quota increases under the 14th General Review. Projected income from the Fixed-Income Subaccount of the Investment Account and interest-free resources are expected to increase more gradually over the medium-term as market indicators now point to a slower rise in interest rates from their current low levels. The expenditure path includes an increase in real terms of about 1\2 percent in the net administrative budget for FY 2017 to accommodate rising costs for physical and IT security. Moreover, reflecting further upward pressure over the medium term and uncertainty about the scope for offsetting savings, the traditional baseline assumption of a constant real spending envelope in the outer years is complemented by an alternative scenario with a further moderate spending increase of 1 1\2 percent, phased in over FY 2018-19. In addition, a lower projected U.S. dollar/SDR exchange rate increases the expenses in SDR terms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet